IMPACT OF ARTIFICIAL INTELLIGENCE ON DIGITAL CONTENT CREATION - P., Vijayalakshmi; V., Vishnu Vardhan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Artificial Intelligence is a significant player in the digital content industry. This article talks about how AI improves content and makes it look finer. The research focuses on how digital content has the potential to be both beneficial and harmful. The researcher examines the cruel aspects of AI if content creators have complete access to AI tools. By observing some of the recently viral digital content and identifying how risky it might be if content creators exploit digital content using AI where people will be entertained but no one will know who generated the specific content. The article looks further at how dangerous it would be if digital content creators used AI techniques to produce content that expresses their vengeance against a specific person and the traumas faced by the victim. The purpose of this article is to explore the potential for AI to cause someone to lose both respect and money. The research will give a complete view of how AI could be a threat to the creation of social content and also will give a detailed view of creating creative minds using AI.